Myrsidea Waterston (Phthiraptera: Menoponidae) from wrens (Passeriformes: Troglodytidae), with descriptions of three new species - Price, Roger D.; Johnson, Kevin P.; Dalgleish, Robert C. (Zootaxa, 2008)
Three new species of Myrsidea parasitic on members of the avian family Troglodytidae are described herein. They and their type hosts are M. whitemani ex the Rufous-naped Wren, Campylorhynchus rufinucha (Lesson, 1838), M. bessae ex the Riverside Wren, Thryothorus semibadius Salvin, 1870, and M. vincesmithi ex the Rufous-breasted Wren, Thryothorus rutilus Vieillot, 1819. Myrsidea troglodyti (Denny, 1842) is redescribed and a lectotype designated. Results of sequencing a portion of the mitochondrial COI gene for one of these species and several other species of Myrsidea are given to compare genetic divergence.